OS 21-03 EFFECTS OF THE TRPM7 KINASE DOMAIN IN VASCULAR DYSFUNCTION AND CARDIAC FIBROSIS INDUCED BY ALDOSTERONE AND SALT. (September 2016) - Rios, Francisco J.; Hood, Katie Y.; Karvey, A.; Neves, Karla B.; Anyfanti, Panagiota; Nosalski, Ryszard; Camargo LL, Livia L.; Montezano, Augusto C.; Touyz, Rhian M.
Abstract : Objective: TRPM7 is cation channel with intrinsic kinase activity important for cellular Mg 2+ homeostasis. We recently showed that TRPM7-kinase plays a role in aldosterone-mediated vascular effects and inflammation. Here we explored the putative role of TRPM7-kinase in cardiac fibrosis and vascular function in aldosterone-induced hypertension in mice. Design and Method: Wild-type (WT) or heterozygote TRPM7-kinase domain (TRPM7+/-) mice were treated with infused aldosterone (600 μg/Kg/day) and NaCl 1% in drinking water (aldo/salt) for 4 weeks. Blood pressure (BP) was evaluated by tail-cuff. Vessel function was investigated in mesenteric resistance arteries by wire and pressure myography. Protein expression of pro-fibrotic molecules was assessed in cardiac tissue by western-blot and histology. Results: Aldo/salt increased BP in TRPM7+/- and WT animals to similar levels (137mmHg vs control group 118mmHg). Mesenteric arteries from untreated TRPM7+/- mice are more sensitive to relaxation induced by acetylcholine (LogEC50: 7.6 ± 0.1 vs 7.1 ± 0.2, TRPM7+/- and WT, respectively), effects that were reduced by Aldo/salt treatment (LogEC50: 7.2 ± 0.1). Phenylephrine-contraction and sodium nitroprusside-relaxation curves were similar among groups. Pressure myography showed that in WT, aldo/salt increase the diameter (26%) and cross-sectional area (40%), resulting in hypertrophic outward remodeling, whereas in TRPM7+/-, the treatment decreased the diameter (16%) and increase the wall/lumen ration (82%), resulting in eutrophic inward remodeling. Regarding to fibrotic markers, untreated TRPM7+/- mice had increased plasma galectin-3 (2.5ng/mL) vs WT (1.4ng/mL) and protein expression for fibronectin (2.4-fold) and TGFβ (2-fold) in hearts, which were similar to WT-aldo/salt. Aldo/salt treatment induced higher collagen expression in TRPM7+/- than in WT animals (15%). Conclusions: Our results suggest anti-fibrotic effects of the TRPM7-kinase domain, since TRPM7+/- mice presented increase in heart fibrotic markers and vascular remodeling compared to WT. Our findings provide some insights into aldosterone signaling through TRPM7-kinase and suggest that this chanzyme may have protective actions, which when downregulated, promotes cardiac fibrosis in aldosterone-induced hypertension.